Performance of Conventional Cytology and Colposcopy for the Diagnosis of Cervical Squamous and Glandular Neoplasias - Giselle Fachetti-Machado; Rosane Ribeiro Figueiredo-Alves; Marise Amaral Rebouças Moreira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To estimate the cytological and colposcopic performances for the diagnosis of cervical neoplasias. Methods Cross-sectional retrospective study with data from patients' charts. The participants underwent colposcopy, guided biopsies, and excision when needed. The cytological and colposcopic categorization followed the Bethesda System and the international colposcopic terminologies. The cytology and colposcopy performances were evaluated by sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV) analyses with 95% confidence interval (95% CI). Results From 1,571 participants, a total of 1,154 (73.4%) were diagnosed with cervical squamous intraepithelial neoplasia grade 2 or worse (CIN 2+), 114 (7.2%) with adenocarcinoma in situ or worse (AIS+), 615 (39.2%) presented atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion or worse (ASC-H+) cytology, and 934 (59.4%) presented major or suspicious for invasion colposcopic abnormalities. The SE, SP, PPV, and NPV of ASC-H+ for diagnoses of CIN 2+ and AIS+ were, respectively: 44% (95% CI: 41-47) and 72% (95% CI: 67-76), 79% (95% CI: 77-81) and 79% (95% CI: 75-83), 88% (95% CI: 87-90) and 55% (95% CI: 50-60), and 28% (95% CI: 26-31) and 88% (95% CI: 85-91). The SE, SP, PPV, and NPV of major or suspicious for invasion colposcopic abnormalities for diagnoses of CIN 2+ and AIS+were, respectively: 62% (95% CI: 60-65) and 86% (95% CI: 83-89), 59% (95% CI: 57-62) and 59% (95% CI: 55-64), 85% (95% CI: 83-87) and 44% (95% CI: 40-49), and 29% (95% CI: 27-32) and 92% (95% CI: 89-94). Conclusion The SE analyses results of ASC-H+ and major or suspicious for invasion colposcopic abnormalities were higher for diagnoses of glandular neoplasias. These results confirm the role of cytology in identifying women at risk who will have their final diagnoses settled by colposcopy and histology.